2017
DOI: 10.5194/gmd-10-105-2017
|View full text |Cite
|
Sign up to set email alerts
|

Connecting spatial and temporal scales of tropical precipitation in observations and the MetUM-GA6

Abstract: Abstract. This study analyses tropical rainfall variability (on a range of temporal and spatial scales) in a set of parallel Met Office Unified Model (MetUM) simulations at a range of horizontal resolutions, which are compared with two satellitederived rainfall datasets. We focus on the shorter scales, i.e. from the native grid and time step of the model through subdaily to seasonal, since previous studies have paid relatively little attention to sub-daily rainfall variability and how this feeds through to lon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…Such forcing will normally be compensated for by subsidence of the surrounding grid cells, resulting in "spotty," disorganized convection. A similar effect was reported by Martin et al (2017), who turned off the cumulus parameterization scheme in a 20 km × 14 km grid model. Conversely, the relatively slow increase in tropospheric mositure and updraft area that occurred 1-2 months after initalization likely reflect the model preference upon forming a near-balanced state over larger horizontal scales.…”
Section: Journal Of Advances In Modeling Earth Systemsmentioning
confidence: 95%
See 2 more Smart Citations
“…Such forcing will normally be compensated for by subsidence of the surrounding grid cells, resulting in "spotty," disorganized convection. A similar effect was reported by Martin et al (2017), who turned off the cumulus parameterization scheme in a 20 km × 14 km grid model. Conversely, the relatively slow increase in tropospheric mositure and updraft area that occurred 1-2 months after initalization likely reflect the model preference upon forming a near-balanced state over larger horizontal scales.…”
Section: Journal Of Advances In Modeling Earth Systemsmentioning
confidence: 95%
“…Optimization of CS and cloud micorphysics scheme parameters should further decrease the model errors, but it remains to be seen whether the schene outperforms NoCS overall after careful tuning. The spottiness of convectivion can be reduced, as suggested by Martin et al (2017). Moreover, it is implied that the sensitivity of convection to environmental moisture, and thus, the model preference to convect over regions rich in mositure supply, can be controlled to a certain extent by changing the parameters of the CS scheme.…”
Section: Journal Of Advances In Modeling Earth Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pacific Decadal Oscillation (PDO) represents variability in the tropical and extratropical North Pacific at interdecadal timescales that significantly impact climate (Mantua et al, 1997;Meehl et al, 2013). Figure 6 shows a regres- Figure 5.…”
Section: Variability Of Precipitation Due To Pdo Enso and East Asianmentioning
confidence: 99%
“…GA6 includes a new dynamical core and updates various physical parameterizations [Walters et al, 2017]. Similarly, Martin et al [2017] analyzed tropical precipitation in GA6 with a range of horizontal resolutions and found that the behaviour of the deep convection parameterization in GA6 is largely independent of the grid-box size and time step length over which it operates. In addition to model physics upgrade, another area of growth in global climate model development is the enhancement of horizontal spatial resolution.…”
Section: Introductionmentioning
confidence: 99%